The Effect of Brand Personality, Brand Awareness, Fashion Consciousness on Loyalty Through Satisfaction as An Intervening Variable - Rimiyati, Hasnah; Rizky Avasyah Rahman, Achmad (Journal of Business and Halal Industry, 2024)
This study aims to analyze the influence of Brand Personality, Brand Awareness, and Fashion Consciousness on Loyalty through Satisfaction as an intervening variable (Study on Consumers of Erigo Fashion Products in Yogyakarta). The subjects in this study were users of Erigo fashion products in Yogyakarta. This research method is quantitative, with data collected through online questionnaires and the variable measurement scale applied to the Likert scale. The type of data used in this study is primary data. In this study, the number of samples was 190 respondents collected using the non-probability sampling method with a purposive sampling technique with the characteristics of Erigo fashion product customers in Yogyakarta with purchases more than 1 time in the last 6 months and a minimum age of 17 years. The analysis tool used is SEM assisted by AMOS 18. Based on the analysis that has been done, the results obtained are that Brand Personality has a positive and significant effect on Satisfaction, Brand Awareness has a positive and significant effect on Satisfaction, Fashion Consciousness has a positive and significant effect on Satisfaction, Satisfaction has a positive and significant effect on Loyalty, Brand Personality does not have a positive effect on Loyalty, Brand Awareness has a positive and significant effect on Loyalty, Fashion Consciousness has a positive and significant effect on Loyalty, Brand Personality has a positive and significant effect on Loyalty mediated by Satisfaction, Brand Awareness has a positive and significant effect on Loyalty mediated by Satisfaction, and Fashion Consciousness has a positive and significant effect on Loyalty mediated by Satisfaction.